2022
DOI: 10.1177/13684302211035437
|View full text |Cite
|
Sign up to set email alerts
|

Backlash against the #MeToo movement: How women’s voice causes men to feel victimized

Abstract: Three studies examined whether perceived increase in women’s “voice” (i.e., being heard and taken seriously about sexual assault) contributes to perceptions of bias against men. In Study 1, both men and women who perceived women to have a greater voice related to sexual assault, perceived greater victimization of men. This relationship was stronger for relatively conservative participants. In Study 2, relatively conservative (but not relatively liberal) participants who read about #MeToo perceived greater men’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The risk, from the perspective of system justification theory, is that policy proposals that destabilize the status quo will trigger citizens' desires for certainty, order, stability, safety, and social cohesion, and this, in turn, will contribute to systemdefensive motivation, especially on the part of conservatives but also in the population as a whole. This system-defensive motivation, we propose, may elicit backlash and perhaps countermobilization (Jost, 2020;Lisnek et al, 2022;Rudman et al, 2012;Yeung et al, 2014). Thus, hierarchy-attenuating policies may be perceived by some (especially political conservatives) as an attack on the way things are and, indeed, the way they "ought to be," insofar as system justification motivation leads people to perceive descriptive norms about the way things are as prescriptive norms about the way they should be (Baryla et al, 2015;García-Sánchez et al, 2019;Jost et al, 2015;.…”
Section: Practical Implications Of Ideology-based Theories Of Policy ...mentioning
confidence: 86%
“…The risk, from the perspective of system justification theory, is that policy proposals that destabilize the status quo will trigger citizens' desires for certainty, order, stability, safety, and social cohesion, and this, in turn, will contribute to systemdefensive motivation, especially on the part of conservatives but also in the population as a whole. This system-defensive motivation, we propose, may elicit backlash and perhaps countermobilization (Jost, 2020;Lisnek et al, 2022;Rudman et al, 2012;Yeung et al, 2014). Thus, hierarchy-attenuating policies may be perceived by some (especially political conservatives) as an attack on the way things are and, indeed, the way they "ought to be," insofar as system justification motivation leads people to perceive descriptive norms about the way things are as prescriptive norms about the way they should be (Baryla et al, 2015;García-Sánchez et al, 2019;Jost et al, 2015;.…”
Section: Practical Implications Of Ideology-based Theories Of Policy ...mentioning
confidence: 86%
“…Political polarization is becoming intensified at a time when a backlash is occurring against the progressive incorporation of different historically disadvantaged groups into public life (Lisnek et al, 2022;Mudde, 2019). Thus, future endeavors might find it useful to discern between political conflicts stemming from dynamics of polarization, and conflicts stemming from the resistance, on the part of unprivileged groups, to a conservative backlash, as the causes, consequences, and interventions that would arise from these different conceptualizations will be different.…”
Section: Discussionmentioning
confidence: 99%
“…In their work, Lisnek, Wilkins, Wilson and Ekstrom (2022) shone light on a specific domain: sexual assault. In particular, they explored how men can claim victimhood for their group, even in contexts in which the topic is men’s assault of women.…”
Section: Preview Of the Special Issuementioning
confidence: 99%
“…Other teams in the Special Issue found shift effects to be stronger among those higher in zero-sum beliefs (e.g., Stefaniak & Wohl, 2022) or when such beliefs are manipulated (e.g., Jones et al, 2022); others observed that dynamics framed in terms of dominant group advantage (vs. less dominant group disadvantage) were particularly threatening to the dominant group (see Dover, 2022). With regard to political partisanship and political ideology, researchers also found stronger pushback against privilege being lost among White Republicans and conservatives (vs. White Democrats and liberals; see Knowles, Tropp and Mogami 2022), or found stronger beliefs that men (vs. women) are victims of the #MeToo movement (e.g., Lisnek, Wilkins, Wilson and Ekstrom 2022). Relatedly, Brown, Rucker and Richeson(2022) found that conservatives were consistently threatened and committed to pushing back, regardless of the presentation of racial shift information; instead, the experimental “action” was observed primarily among liberals, who became less psychologically rattled in the shift (vs. control) conditions, seemingly embracing the change in demographics and/or power.…”
Section: Special Issue Themesmentioning
confidence: 99%
See 1 more Smart Citation